Thermal Solution Depolymerization of RAFT Telechelic Polymers - De Alwis Watuthanthrige, Nethmi; Whitfield, Richard; Harrisson, Simon; Truong, Nghia P; Anastasaki, Athina (ACS macro letters, 2024)
Thermal solution depolymerization is a promising low-temperature chemical recycling strategy enabling high monomer recovery from polymers made by controlled radical polymerization. However, current methodologies predominantly focus on the depolymerization of monofunctional polymers, limiting the material scope and depolymerization pathways. Herein, we report the depolymerization of telechelic polymers synthesized by RAFT polymerization. Notably, we observed a significant decrease in the molecular weight ( ) of the polymers during monomer recovery, which contrasts the minimal shift observed during the depolymerization of monofunctional polymers. Introducing Z groups at the center or both ends of the polymer resulted in distinct kinetic profiles, indicating partial depolymerization of the bifunctional polymers, as supported by mathematical modeling. Remarkably, telechelic polymers featuring R-terminal groups showed up to 68% improvement in overall depolymerization conversion compared to their monofunctional analogues, highlighting the potential of these materials in chemical recycling and the circular economy.